2009
DOI: 10.1021/bi802046n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a Soluble Amyloid β-Peptide Oligomer

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder that is linked to the presence of amyloid beta-peptides that can form insoluble fibrils or soluble oligomeric assemblies. Soluble forms are present in the brains and tissues of Alzheimer's patients, and their presence correlates with disease progression. Long-lived soluble forms can be generated in vitro by using small amounts of aliphatic hydrocarbon chains of detergents or fatty acids in preparations of amyloid beta-peptides. Using NMR, we have charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
401
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(447 citation statements)
references
References 39 publications
42
401
2
2
Order By: Relevance
“…Our observations suggest that self-assembling of Ab(1-40) from oligomers to fibrils involves the central (aa [17][18][19][20][21][22][23][24] and C-terminal parts (aa 30-40) of the peptide (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our observations suggest that self-assembling of Ab(1-40) from oligomers to fibrils involves the central (aa [17][18][19][20][21][22][23][24] and C-terminal parts (aa 30-40) of the peptide (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
“…Despite the general interest concerning oligomers toxicity compared to fibrils, few structural data are available [17,18] and so far, no consensus model has been proposed. Nevertheless, infrared spectroscopy on Ab(1-40) [19] and [20,21] oligomers shows an antiparallel b-sheet organization.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated Aβ isolated from the brains of AD patients contains neurotoxic dimeric and trimeric species that are either formed in SDS-containing solutions or are resistant to denaturation in SDS/ PAGE electrophoresis experiments. It has been suggested that such species may constitute building blocks of toxic Aβ aggregates (3,18). If this suggestion is true and if the aggregates formed by AβCC are structurally identical to wild-type aggregates, then one would expect AβCC to form SDS-stable dimers.…”
Section: Resultsmentioning
confidence: 99%
“…There is also experimental evidence for the hairpin in oligomers of the globulomer kind (18), as well as for antiparallel β-sheet secondary structure in Aβ oligomers formed in TBS buffer or in cell culture medium (19). We therefore set out to test if stabilizing Aβ in the hairpin conformation observed in the Affibody complex would promote the formation of oligomeric aggregates but not fibrils, and whether such stabilized oligomers would possess antigenic and neurotoxic characteristics similar to those of wild-type Aβ oligomers found in AD.…”
mentioning
confidence: 99%
“…This particular type of association might be favored for M35C because this mutation stabilizes the C-terminal parallel β-sheet characteristic for Aβ-globulomers corresponding to 12À16 peptides/soluble aggregate. 19 To investigate the homogeneity of the Aβ oligomers under native conditions, we purified the secreted Aβ oligomers by size exclusion chromatography (SEC) and Western blotted the fractions. By performing this analysis, we demonstrated that APP(AβS8C) was processed to yield exclusively dimeric Aβ (Figure 3c), whereas the M35C was assembling to a greater variety of high molecular weight species similar to the results in SDS-PAGE/Western blotting (Figure 3a, c).…”
Section: ' Results and Discussionmentioning
confidence: 99%